ANALISIS STATUS GAKY DAN ASPEK KESEHATAN YANG BERHUBUNGAN DENGAN PRESTASI BELAJAR ANAK SEKOLAH DASAR DI DAERAH ENDEMIS GAKY - Purnamasari, Dyah Umiyarni; Dardjito, Endo; Kusnandar, Kusnandar (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2015)
ABSTRACTThe risk of School children in Iodine Deficiency Disorders (IDD) endemic areas will decrease of learning achievement . Objective of this study was to analyze the status of IDD and health aspects associated with school children's learning achievement base IDD in endemic areas .The method was used a cross-sectional approach . Population of this study were all Rempoah primary school children, there are 178 children , while the samples were taken by purposive sampling of 33 fourth grade students at SDN I Rempoah Baturaden . The results showed all samples of students there were no have an enlarged thyroid gland through a large palpasi. Although Chi Square analysis test showed no relationship in all variables, but using cross tabulating we can see which samples who have genetic family of IDD have low good learning achievement (66,7 %) than none (84,6 %), samples who have poor nutritional status have low learning achievement (57,1 %) than good one (84,6 %) and samples who have low physical fitness have low good learning achievement(75,9 %) than good physical fitness (100 %) . Suggested more activity level for increase physical fitness .Keywords : IDD, Nutritional Status, School Children Kesmasindo, Volume 7(2), Januari 2015, Hal. 71-81